Corona Virus Legal Protection For Patients According To Law No. 44 Year 2009 Concerning Hospital - Michelle Angelika S; St. Laksanto Utomo (CV. Publikasi Indonesia, 2021)
The COVID-19 epidemic that struck Indonesia has had farreaching consequences for the Indonesian people in terms of health, legal, social issues, and so on. Because of the virus's rapid transmission, patients who are infected are entitled to legal protection under Law No. 44 of 2009. The hospital's responsibility to coronavirus patients is to provide all patient rights as outlined in the applicable laws and regulations. Sanctions will be imposed in accordance with existing rules and regulations if this is not done.